Engaging Research Groups: Rethinking Information Literacy for Graduate Students. - Bonnie L. Fong; Darren B. Hansen (Issues in Science and Technology Librarianship)
Librarians have traditionally taught information literacy skills to science graduate students in separate courses dedicated to information-seeking, during assignment(s)-based library sessions for other courses, or through workshops. There is little mention in the professional literature of teaching graduate students within their research groups. This is certainly an alternative to consider -- especially for smaller science graduate programs where the more traditional means of reaching graduate students are less likely. This article discusses a collaborative effort between a Chemistry professor and Physical Sciences Librarian at Rutgers University-Newark to design a mini-course for a research group. With the amount of customization possible when working with research groups, this option may even become increasingly significant due to the growing importance of interdisciplinary research. [ABSTRACT FROM AUTHOR]